Employee Performance: Effects of Competence and Compensation: Study At One of The Local Government Agencies in Bandung Regency - Mulyani, Sri; Nurhadian, Adhie Fasha (Acman: Accounting and Management Journal, 2023)
The purpose of this research is to determine and analyze employee competency, employee compensation, employee performance, the extent of the influence of competency on employee performance, the extent of the influence of compensation on employee performance, and the extent of the influence of competency and compensation on employee performance in one of the local government agencies in Bandung Regency. The research method used by the author is descriptive and verification research to identify the significant relationship between the variables under investigation, thus producing conclusions that will describe the object being studied. The research results show that competency has a total influence on employee performance of 7.2%, while compensation has a total influence on employee performance of 70%. The total influence of the independent variables on the dependent variable is 77.2%, while the remaining 22.8% is influenced by other variables outside the scope of this study. The implications of the research indicate that having good competency combined with adequate compensation can enhance employee performance.